Atherogenic ApoB-dyslipidemia, atherosclerotic cardiovascular disease, cardiac dysfunction and remodeling in high-risk young women with and without polycystic ovary syndrome: A pilot study - Wu, Xiaoying; Wilke, Mich; Batara, Jesse; Proctor, Spencer; Cree, Melanie; Ghosh, Mahua; Raggi, Paolo; Windram, Jonathon; Becher, Harald; Vine, Donna (Frontiers in Endocrinology, 2025)
IntroductionPolycystic ovary syndrome (PCOS) is associated with increased cardiometabolic risk in young women of reproductive age. There are limited studies on atherogenic dyslipidemia, inclusive of triglycerides (TG), Apolipoprotein (apo) B-lipoproteins and remnant-cholesterol (C), atherosclerotic cardiovascular disease (ACVD), cardiac function and remodeling in young women with and without PCOS. The aim of this pilot study was to investigate the relationship of atherogenic dyslipidemia and other cardiometabolic risk factors with ACVD, cardiac function-remodeling in high-risk young overweight-obese PCOS women compared to non-PCOS and healthy-weight controls.MethodsWomen with and without PCOS (non-PCOS control) aged 18 – 45 years who were overweight and obese (>25kg/m2) were matched for age and BMI, and by age with healthy-weight non-PCOS controls. PCOS diagnosis was based on Rotterdam criteria. Fasting lipids and non-fasting plasma lipid assessment included TG, remnant-C, total ApoB, ApoB48 and ApoB100. Carotid intimal-medial thickness (cIMT) and carotid plaque height were assessed, and cardiac function and remodeling were measured by 2-D ultrasound and 3D-echocardiography.ResultsPCOS (n=48) and non-PCOS control overweight-obese age-BMI matched groups (n=19) were shown to have significantly higher fasting and non-fasting lipids including TG, remnant-C, total ApoB and ApoB48, compared to healthy-weight non-PCOS controls (n=10). PCOS and non-PCOS control overweight-obese groups had significantly higher SBP, DBP, cIMT and evidence of cardiac dysfunction and remodeling, with reduced Mitral E/A ratio, intraventricular (IV) relaxation time and increased Left ventricle (LV) end diastolic and systolic diameter, LV posterior wall thickness and IV septal thickness, compared to healthy-weight non-PCOS controls. Individuals with PCOS had significantly higher fasting plasma TG and remnant-C compared to the non-PCOS overweight-obese control group. The PCOS group tended to have 25% higher carotid plaque height, although this was not significant, compared to the non-PCOS overweight-obese control group. DBP, HOMA-IR and ApoB predicted 40% of the variability in cIMT and ApoB was shown to predict 14% of the variability in carotid plaque height, independent of age and BMI. A 1mg/ml increase in ApoB was associated with a 0.041mm increase in cIMT and a 0.75mm increase in carotid plaque height in all young women.DiscussionOur pilot results supports the potential of apoB-dyslipidemia, cIMT, carotid plaque height and left ventricular diastolic dysfunction and remodeling to be used in screening for CVD risk in high-risk populations such as overweight-obese women with and without PCOS. ApoB may be useful to predict atherosclerotic vascular burden and progression of cIMT and carotid plaque, and could be used to develop a female specific algorithm for ACVD risk in high-risk young women with and without PCOS.